2021
DOI: 10.3332/ecancer.2021.1214
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with advanced stage diagnosis of breast cancer in North West Ethiopia. a cross-sectional study

Abstract: Background: Breast cancer tumours are the most common malignant tumours among women in Ethiopia. Although advanced-stage diagnosis of breast cancer is a common problem, evidence-based information is lacking about the magnitude and determinants of advanced-stage presentation in north-west Ethiopia.Methods: An institution-based, cross-sectional study was conducted at the oncology units of the University of Gondar and Felege Hiwot specialised hospitals. Stages III and IV were considered advanced stage, whereas st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
4
23
1
Order By: Relevance
“…This finding was in agreement with a prior study conducted among female healthcare professionals in Nigeria (28). However, knowledge of BSE and BC was significantly associated with BSE practice in studies conducted among healthcare professionals in Ethiopia (15,24,31) and Turkey (32).…”
Section: Discussionsupporting
confidence: 92%
“…This finding was in agreement with a prior study conducted among female healthcare professionals in Nigeria (28). However, knowledge of BSE and BC was significantly associated with BSE practice in studies conducted among healthcare professionals in Ethiopia (15,24,31) and Turkey (32).…”
Section: Discussionsupporting
confidence: 92%
“…This nding was in ≥ agreement with a prior study conducted among female healthcare professionals in Nigeria (28). However, knowledge of BSE and BC was signi cantly associated with BSE practice in studies conducted among healthcare professionals in Ethiopia (15,24,31) and Turkey (32).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, other three studies with much less sample sizes (one in Thailand, one in Colombia and one in Korea) concluded that older patients had higher odds of getting diagnosed at late stages compared to younger patients (3638). Moreover, four other studies that have been conducted in three African countries (two in Nigeria, one in South Africa, and one in Ethiopia) concluded that age was not significantly associated with advanced stage diagnosis of BC (4,5,39,40).…”
Section: Methodsmentioning
confidence: 97%